Optimizing Academic Advisor Roles Via E-mentoring At English Department of Universitas Negeri Makassar - Nurul Azizah Iqbal; Kisman Salija; Samtidar Samtidar (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research examines the Optimizing Academic Advisor Roles Via E- mentoring at English Department of Universitas Negeri Makassar. The researchers applied descriptive qualitative method. The subject of this research was the 2nd, 4th, 6th, 8th semester students from English Education class Pare-Pare. The subjects consist of 10 students which were taken by using purposive random sampling technique. The data obtained through interview which were analysed qualitatively in several stages, namely data reduction, data display, and drawing conclusion and verification to find accuracy data. The result of data analysis showed that based on the interview which had been taken via WhatsApp, it can be said that this study demonstrates that e- mentoring has promise as a vehicle for preparing study plans, giving consideration in choosing courses programmed, guiding in approving the study plan, solving personal, social, and career problems via E-mentoring during Covid-19 pandemic such as WhatsApp.